System Design of the EDEN LUNA Greenhouse: Upgrading EDEN ISS for future Moon mission simulations - Vrakking, Vincent; Philpot, Claudia; Schubert, Daniel; Aksteiner, Niklas; Strowik, Christian; Ksenik, Eugen; Sasaki, Kaname; Toth, Norbert; Franke, Michel Fabien; Bunchek, Jess Marie; Bornemann, Gerhild; Holbeck, Ilse Marie; et al. (2024)
The joint DLR-ESA project LUNA aims to develop a facility to simulate future lunar surface exploration missions. As part of this project, the EDEN LUNA project will modify the EDEN ISS semi-closed space analogue greenhouse, which has previously been operated at the German Neumayer Station III in Antarctica from 2018 until 2022, for operation at the LUNA facility in Cologne, Germany. The EDEN ISS Mobile Test Facility will be refurbished and outfitted with updated Controlled Environment Agriculture technologies based on lessons learned from operations in the Antarctic. Additionally, EDEN LUNA will integrate and test two new main payloads. The first payload, the EDEN Versatile End-Effector, will test the use of a robotic arm and hand on a linear rail system for automated plant health monitoring and plant handling. The second payload, the C.R.O.P.® biofilter, will demonstrate conversion of urine into nutrient solution for plant cultivation. This paper introduces the EDEN LUNA project and describes the preliminary system design of the EDEN LUNA greenhouse.